COMPARATIVE ANALYSIS OF SULAYMAN BAKIRGANI AND "BOOK OF BAKIRGAN" BASED ON FOREIGN SOURCES - Ismoilov Kahramonjon (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article talks about the life and the work of Sulayman Bakirgani, his book "Hakim Ata" and how it was studied by foreign scientists, and the American scientist D.DeWeese's and Turkish scholar F.Kuprulu’s opinions about the "Book of Bakirgani" is analyzed.